A simple, physically motivated model of sea-level contributions from the Greenland ice sheet in response to temperature changes. (September 2016) - Bakker, Alexander M.R.; Applegate, Patrick J.; Keller, Klaus
Abstract: Sea level could rise by several meters over the next centuries. The Greenland ice sheet could be an important contributor to future sea-level rise, because of its large volume and its high sensitivity to surface air temperature increases. Frameworks for the integrated climate risk management often require fast, simplified treatments of sea-level rise, in particular for estimating the risks associated with low probabilities but potentially high impacts. State-of-the-art ice sheet models provide important insights, but are often computationally too demanding to evaluate tail-area risks. Here we present SIMPLE, a physically motivated model of the Greenland ice sheet in response to temperature changes. SIMPLE can skillfully reproduce the results from a three-dimensional ice sheet model and outperforms existing simple models, after similar calibration. We anticipate that SIMPLE will be calibrated to other ice sheet models and can provide a fast approximation (emulator) for such models in studies that require many model evaluations. Highlights: SIMPLE is a fast physically motivated model of the Greenland ice sheet. It provides fast approximations in studies that require many model evaluations. It skillfully reproduces 3D ice sheet model simulations over a wide range of forcings. SIMPLE outperforms existing simplified representations, after similar calibration.